Pelatihan Pembelajaran Mendalam Matematika di MIS Darul Mustofa Jember - Muhlisatul Mahmudah; Tri Novita Irawati; Sholahudin Al Ayubi (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
The rapid advancement of digital technology and the implementation of the Deep Learning approach require educators to be capable of designing meaningful, student-centered mathematics learning while integrating digital technology pedagogically. However, many teachers and pre-service teachers still face difficulties in developing learning materials that align with the characteristics of Deep Learning. This community service program aimed to enhance participants' competence through training and mentoring activities. The program employed a participatory training approach consisting of needs assessment, instructional sessions, discussions, hands-on practice in developing learning materials, mentoring, and evaluation using pre-tests, post-tests, observations, product assessment, and participant satisfaction questionnaires. The results showed an improvement in participants' understanding of the Deep Learning concept and their ability to develop mathematics learning materials that incorporate the principles of mindful learning, meaningful learning, and joyful learning through the effective use of digital technology. The primary output of this program was mathematics learning materials that are ready to be implemented in classroom practice. This program contributed to improving educators' professional competence and supported the implementation of Deep Learning to promote higher-quality mathematics learning that is relevant to the demands of the digital era.